A Conceptual Framework For Employee Performance In The Islamic Hospitality In Indonesia - Nisa'u Lailatizzahro; Naning Kristiyana; Adi Santoso (Jurnal Manajerial, 2023)
Background – There are pressures experienced by Islamic hospital employees in Indonesia who are exposed to negative workplace gossiping and toxic leadership has an effect on the performance of Islamic hospital employees in Indonesia. These problems can be minimized by applying an Islamic work ethics in order to improve the employees performance of Islamic hospital in Indonesia. Purpose – The purpose of this study was to determine the performance of employees at the Indonesian Islamic Hospital. Design/ Methodology/ Approach – This study uses the COR basis in analyzing phenomena and research findings. The population of this study was medical staff throughout the Indonesian Islamic Hospital. The number of samples was determined using the Isaac equation table so that a total sample of 300 respondents was obtained. Retrieval of data using questionnaires that are distributed online. Measurement data uses answers Strongly Agree, Agree, Netral, Disagree, Strongly Disagree, with a rating scale of 1 to 5 Data processing uses the SMART PLS3 application. Findings – The findings of this study revealed that staff performance at the Indonesian Islamic Hospital is significantly impacted by toxic leadership negative workplace gossiping, and islamic work ethics. This can be seen from the results of the discriminate validity test and the final results of Smart PLS3 data processing. Conclusion – The study's findings are consistent with another study that found that Indonesian Islamic Hospital employees perform better when they adhere to islamic work ethics has a significant positive effect on Employee Performance. Meanwhile, toxic leadership and negative workplace gossiping significant negative effect on employee performance at the Islamic Hospital in Indonesian. Research Implication – The results of this study are expected to be input for managers in Islamic Hospitals in Indonesia, especially knowing the effect of Islamic work ethics, Toxic Leadership, Negative Gossip in the Workplace on employee performance as an intervening variable, becoming learning material and applying knowledge in the field of management, especially in the field of management of human resources and can be an additional reference for further research and as a consideration for Islamic Hospitals in Indonesia which are facing similar problems. Research Limitations – The results of this study can be an opportunity for further research development by focusing on more specific target respondents and adding variables that have a role in Islamic work ethics, toxic leadership, and negative workplace gossiping to improve employee performance at the Indonesian Islamic Hospital.